Answer:
-1
Step-by-step explanation:
"Consecutive" means one after the other. Let the lesser number = x, while the greater number = x + 1 (as it is directly after the lesser number).
Set the equation:
x * (x + 1) = 156
Simplify. Distribute x to both terms within the parenthesis:
x(x + 1) = 156
x² + x = 156
Set the equation = 0. Subtract 156 from both sides:
x² + x (-156) = 156 (-156)
x² + x - 156 = 0
Solve for x.
x² + x - 156 = 0
x 13
x - 12
(x + 13)(x - 12) = 0
Solve for x. Set each parenthesis = 0. Isolate the variable, x.
x + 13 = 0
x + 13 (-13) = 0 (-13)
x = -13
x - 12 = 0
x - 12 (+12) = 0 (+12)
x = 12
x = -13 , 12.
Solve for their sum. Add:
-13 + 12 = -1
-1 is your answer.
~